Bacteremia por Staphylococcus epidermidis y abceso de partes blandas en un paciente postoperado: Reporte de un caso. - GARCIA APAC, Coralith (Revista Médica Herediana, 2013)
We report a case of an 11 year old male who presented with bacteremia by S. epidermidis and soft tissue abscesses after a bone autograft procedure. The patient received only medical treatment, resolving the abscesses successfully. We also did a review of the literature on S. epidermidis bacteremia, an entity which has acquired increasing importance in the etiology of hospital infections. (Rev Med Hered 2003; 14:221-223)